Identification of Contaminated Cells with Viruses, Bacteria, or Fungi by Fourier Transform Infrared Microspectroscopy - V. Erukhimovitch; M. Huleihil; M. Huleihel (Journal of Spectroscopy)
Fourier transform infrared microspectroscopy (FTIR-M) can detect small molecular changes in cells and therefore was previously applied for the identification of different biological samples. In the present study, FTIR spectroscopy was used for the identification and discrimination of Vero cells infected with herpes viruses or contaminated with bacteria or fungi in cell culture. Vero cells in culture were infected herpes simplex virus type 1 (HSV-1) or contaminated with E. coli bacteria or Candida albicans fungi and analyzed by FTIR microscopy at 24 h postinfection/contamination. Specific different spectral changes were observed according to the infecting or contaminating agent. For instance, both pure fungi and cell culture contaminated with this fungi showed specific peaks at 1030 cm−1 and at 1373 cm−1 regions, while pure E. coli and cell culture contaminated with this bacteria showed a specific and unique peak at 1657 cm−1. These results support the potential of developing FTIR microspectroscopy as a simple, reagent free method for identification and discrimination between different tissue infection or contamination with various pathogens.